1979
DOI: 10.1073/pnas.76.10.5336
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive enzymatic radioimmunoassay: application to detection of cholera toxin and rotavirus.

Abstract: Rotavirus and enterotoxin-producing bacteria are major causes of diarrheal disease in humans. A method of rapid diagnosis, ultrasensitive enzymatic radioimmunoassay, has been developed to quantitatively detect cholera toxin and rotavirus. The method uses features of both enzyme-linked immunosorbent assay and radioimmunoassay; however, the sensitivity of the assay is 100-to 1000-fold more sensitive than the two parent assays. Ultrasensitive enzymatic radioimmunoassay should also be useful in measuring other bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…These sensitivities are much higher than those of previously reported methods for assay of TDH (14), Shiga toxin (19), and cholera enterotoxin (7), and are comparable to that for Shiga toxin reported by Donohue-Rolfe et al (4) and that for cholera enterotoxin reported by Harris et al (6). Variation in sensitivity with different toxins has been repeatedly observed with different immunized rabbits.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…These sensitivities are much higher than those of previously reported methods for assay of TDH (14), Shiga toxin (19), and cholera enterotoxin (7), and are comparable to that for Shiga toxin reported by Donohue-Rolfe et al (4) and that for cholera enterotoxin reported by Harris et al (6). Variation in sensitivity with different toxins has been repeatedly observed with different immunized rabbits.…”
Section: Discussioncontrasting
confidence: 42%
“…A good method should be simple, accurate, reproducible, cheap, and sensitive. In general, immunological methods are better than others, and of the various immunological methods so far reported (3,5,6,9,21,27,31), ELISA is the most widely used, because it is the most sensitive, accurate, and reproducible. The sensitivities of the ELISA's reported previously, however, varied significantly.…”
Section: Discussionmentioning
confidence: 99%
“…by liquid or solid extraction procedures) prior to assay in order to obtain reliable data. Alternatively, the assay can be made more sensitive to permit analyses of smaller quantities of a compound (13).…”
Section: Source Of Analytementioning
confidence: 99%
“…First it must be noted that similar sensitivity claims were made for 2 methods described in reports published some 30 years ago (4,5 ). Both methods relied on enzymes as signal amplifiers.…”
mentioning
confidence: 99%